(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the development of professional competencies of future primary education teachers during pedagogical practice. The study highlights the role of pedagogical practice as a key stage in the process of professional formation, where theoretical knowledge is transformed into practical skills. It emphasizes the importance of reflective activity, self-analysis, and innovative pedagogical technologies in improving students’ readiness for independent professional work. The research identifies the conditions, principles, and methods that ensure the effective development of professional competencies, such as communication, creativity, pedagogical thinking, and classroom management. The findings contribute to improving the quality of teacher training and preparing future educators to meet the challenges of modern education.